1975
DOI: 10.1017/s0031182000048873
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of host antigens by youngSchistosoma mansoniin mice: correlation with failure to bind antibodyin vitro

Abstract: Young schistosomes collected after penetration through isolated mouse skin (3 h schistosomula) were cultured in medium containing immune rhesus monkey serum with a high titre of antibody known to kill schistosomula in the presence of complement. Morphological signs of damage in electron micrographs were confined to the surface tegument of the schistosomula. Antibodies in immune rhesus serum were shown to bind to the surface membrane of 3 h schistosomula using an antibody-enzyme bridge technique involving label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…For example, the schistosomula of S. mansoni measure 50 x 400 ,um and consist of more than 1,000 cells. Furthermore, the parasite is limited by a heptalaminar membrane which undergoes biochemical and immunologic alterations as it migrates within the host or during in vitro cultivation (31,32). This organism with its complex surface represents, therefore, a formidable biochemical and ultrastructural barrier to host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the schistosomula of S. mansoni measure 50 x 400 ,um and consist of more than 1,000 cells. Furthermore, the parasite is limited by a heptalaminar membrane which undergoes biochemical and immunologic alterations as it migrates within the host or during in vitro cultivation (31,32). This organism with its complex surface represents, therefore, a formidable biochemical and ultrastructural barrier to host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…However such a premise is not compatible with data derived from in uitro studies which have shown that soon after penetrating the skin, schistosomula acquire several mechanisms for evading the immune response (McLaren 1984). Foremost amongst these are reduced surface antigenicity (McLaren, Clegg & Smithers 1975) and the development of an intrinsic insusceptibility to immune attack (Moser, Wassom & Sher 1980). The possession of these evasive strategies by lung stage schistosomula and to a lesser extent by adult worms, has resulted in their being considered insusceptible to immune attack and it has been assumed that all post-lung forms would similarly be invulnerable.…”
Section: Introductionmentioning
confidence: 92%
“…(1980) have shown that host molecules are demonstrable in the outer membrane as intramembranous particles, which form characteristic aggregates in the presence of anti-host antibodies. Uptake of host molecules both in vivo and in vitro is associated with a corresponding decline in the capacity of the organisms to bind antibodies present in immune serum (McLaren et al 1975), suggesting that such uptake may indeed be sufficient to mask parasite determinants, although Goldring et al (1977) have demonstrated some binding of immune serum to adult worms.…”
Section: Mechanisms Of Evasionmentioning
confidence: 99%